Analisis Jaminan pada Pembiayaan Muá¸Ärabah dalam Perspektif MaqÄá¹£id Al-SyariÌ„â€˜ah - Lestari, Dini Maulana (Al-Manahij: Jurnal Kajian Hukum Islam, 2019)
This paper analyzes the concept of muá¸Ärabah as the main product in sharia banking, where the financing product should be excellent in its marketing. However, muá¸Ärabah financing products are often faced with complicated portfolios and low market shares because they are indicated by high levels of financial risk. To bridge this, collateral is one of the tools used by the Sharia Bank in order to minimize these risks. This type of research is literature with a qualitative-explorative descriptive approach. The results showed that the collateral in muá¸Ärabah financing functions as a Shariah Bank intervention tool to create benefits for creditors and debtors in the event of default in their business, also to avoid moral hazard activities and asymmetric information.